2
$\begingroup$

there is two wrong statement that I want to find counterexample for them. if $\alpha$ and $\beta$ and $\gamma$ be infinite cardinals then show that these two statements are wrong

  • $\alpha < \beta \Longrightarrow \alpha^\gamma < \beta^\gamma$

for this one if $\alpha = \aleph_0$ and $\beta = \gamma = \aleph_1$ then we have $\aleph_1^{\aleph_1} = (2^{\aleph_0})^{\aleph_1} = 2^{\aleph_0 \aleph_1} = 2^{\aleph_1}$ and because $2^{\aleph_1} \leq \aleph_0^{\aleph_1} \leq \aleph_1^{\aleph_1}$ we have that $\aleph_0^{\aleph_1} = \aleph_1^{\aleph_1}$. is this right?

and the second one is

  • $\alpha < \beta \Longrightarrow 2^\alpha < 2^\beta$

for this one if $card(A) = \alpha$ and $card(B) = \beta$ we have that $2^\alpha = card(P(A))$ and $2^\beta = card(P(B))$ and I think this statement is true when $\alpha < \beta$ then $card(P(A)) < card(P(B))$ is this right?

it's from Iran national exam of Computer Science of two years ago.

$\endgroup$
  • $\begingroup$ The second one looks tempting, but I'd suspect that it depends. $\endgroup$ – Hagen von Eitzen Apr 3 '16 at 11:12
4
$\begingroup$

(I'll assume choice throughout.)

You're assuming the continuum hypothesis in saying that $\aleph_1 = 2^{\aleph_0}$; I don't know if you're allowed to do that.

If $\gamma > 2^{\aleph_0}$ then we can use $$2^{\gamma} \leq \aleph_0^{\gamma} \leq (2^{\aleph_0})^{\gamma} = 2^{\aleph_0 \gamma} = 2^{\gamma}$$ so equality holds throughout, and in particular $$\aleph_0^{\gamma} = (2^{\aleph_0})^{\gamma}$$ even though $\aleph_0 < 2^{\aleph_0}$.

For the second one: I don't believe your argument, I'm afraid, because it's possible to force $2^{\aleph_0} = 2^{\aleph_1}$, so it's relatively consistent that there is a counterexample.

However, the Generalised Continuum Hypothesis says that $2^{\alpha} = \alpha^+$, so under GCH we would have that $\alpha < \beta \Rightarrow \alpha^+ < \beta^+ \Rightarrow 2^{\alpha} < 2^{\beta}$. It's (relatively-to-ZFC) consistent that GCH holds, so it's relatively consistent that there are no counterexamples.


Notice that any counterexample for the second one will give you a counterexample for the first one, since $2^{\beta} \leq \beta^{\beta} \leq 2^{\beta \times \beta} = 2^{\beta}$, so equality holds throughout.

Therefore letting $\beta = \gamma$, if we have $\alpha < \beta$ such that $2^{\alpha} \geq 2^{\beta}$, then we have $\alpha < \beta$ such that $2^{\alpha} \geq \beta^{\beta} = \beta^{\gamma}$.

| cite | improve this answer | |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.